Analysis of the Urgency of Hajj and Umrah Bookkeeping in Realizing Professional Financial Governance - Abd Qodir; Mohammad Zainullah; Moh. Affan (DAAR EL-KAMIL: Multidisciplinary Journal, 2026)
The rapid growth of the Hajj and Umrah service industry in Indonesia has increased the need for professional financial governance to ensure transparency, accountability, and public trust. This study aims to analyze the urgency of bookkeeping in realizing professional financial governance within Hajj and Umrah management institutions, particularly PT Qiblatain Safarina Bakti. The research employs a qualitative approach using a literature review method by examining relevant national and international scholarly publications related to bookkeeping, financial accountability, transparency, and organizational governance. The findings indicate that the initial understanding of bookkeeping among many Hajj and Umrah service providers was generally limited to simple financial recording activities and had not yet functioned as a comprehensive financial information system. The implementation of systematic bookkeeping contributes significantly to improving financial transparency, strengthening accountability, enhancing internal control mechanisms, and supporting evidence-based managerial decision-making. Furthermore, bookkeeping is increasingly perceived as a strategic governance instrument rather than merely an administrative requirement, particularly in institutions responsible for managing pilgrims’ entrusted funds. The study concludes that bookkeeping plays a vital role in strengthening organizational credibility, stakeholder confidence, and long-term sustainability. Therefore, Hajj and Umrah institutions should prioritize standardized bookkeeping systems, improve accounting competencies, and adopt digital financial technologies to achieve professional and accountable financial governance.